(3efGbH GdCHQGQ heMGSf GdCNjGQs - (3GdMSjf Hf fUQ, ef Hfj NejS GdcYHqj GdehUdqj GdLgfqj , GpHf nNpejS,J (B552 (3g` s ((3GdEScfOQjI s)
(3ChdgG (B:s
(3CeG HYO aEf efGbH GdCHQGQ CcKQ ef Gf JMUi hWHbGJge GdeUfaI aj gPG GdTCf Ld ef Cf JSJbUi, aQCjJ Cf CaQZ hSYi s
(3BNQgG (B:s
(3gPG eG GfJgi GdjfG ef gPG GdcJGH GdPi Sej efGbH GdCHQGQ hGdUGdMjf s
(3GdUaMI GdChdi efgG HNW eZGjQ hYdjgG bQGAGJ efgG bQGAI CHj HcQ Hf Hf jMj GdQjOj SfI (B702 (3g`s
(3GfXQ HQbe (B828 (3hQbe (B1250 (3JGQjNs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs